Intracranial pressure is elevated at 24 h post‐stroke in mice - Kirby E. Warren; Rebecca J. Hood; Fredrick R. Walker; Neil J. Spratt (Neuroprotection, 2024)
Abstract Background It has long been assumed that post‐stroke intracranial pressure (ICP) elevation occurs because of large infarct and edema volumes. However, we have repeatedly shown ICP elevation at 24 h post‐stroke in the presence of little to no edema in rats. Biological processes are often conserved across species and types of injury. Therefore, we aimed to determine if an ICP rise occurs at 24 h post‐stroke in the presence of small infarct and edema volumes in mice. Methods Mice were randomized by random number table to either photothrombotic stroke or sham surgery (n = 15). Epidural ICP was recorded using a fiber optic catheter at 1 h post‐stroke (baseline) and between 23 and 24 h post‐stroke. Results ICP was significantly higher at 24 h compared to baseline in stroke animals (n = 6; 10.71 ± 6.45 mmHg vs. 3.74 ± 2.20 mmHg, respectively; p = 0.03). ICP at 24 h was also significantly higher in stroke mice compared to sham (n = 6; 3.45 ± 1.43 mmHg; p = 0.02). There was no change in ICP in sham mice (p = 0.9). Edema volumes in stroke animals were small (0.04 ± 0.04 mm3) and unlikely to have caused significant ICP elevation. Conclusion This study provides evidence of an edema‐independent ICP elevation following small ischemic stroke in mice. The occurrence of this rise supports our findings in other species and suggests it is caused by a previously undescribed mechanism.